A robot inspired by a non‐smooth point mass model of a worm. Issue 1 (15th March 2018) - Winandy, Tom; Eugster, Simon R.; Bergold, Markus
Abstract: A non‐smooth point mass model which mimics the locomotion of an earthworm is presented. The planar model consists of a chain with five elements on a rough ground. The distance between each pair of neighbouring elements is restricted by unilateral constraints. The contacts between the elements and the ground are subjected to anisotropic Coulomb friction. First, the equations of motion governing the impact‐free motion are derived. Then, the impact equations are formulated which, together with the generalized Newton's impact law, describe the dynamics at instantaneous impacts. (© 2017 Wiley‐VCH Verlag GmbH & Co. KGaA, Weinheim)